FIEs and the Transmission of Global Financial Uncertainty: Evidence from China - Wu, Shujie; Ye, Haichun (Journal of Financial and Quantitative Analysis, 2023)
This article provides micro-level evidence for the role of foreign-invested enterprises (FIEs) in the cross-border transmission of global financial uncertainty shocks. Using Chinese firm-level data, we find that rising uncertainty has a significantly larger contractionary effect on real investment for FIEs than their local counterparts. This effect is more pronounced for firms faced with greater investment irreversibility or financial constraints. The contractionary effect is mainly driven by downside uncertainty, whereas upside uncertainty is modestly expansionary. Similar effects are found for other firm-level performances. There is also a spillover effect to local private firms with FIEs concentrated in downstream sectors.